2009
DOI: 10.1016/j.carres.2009.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Sulfonation of papain-treated chitosan and its mechanism for anticoagulant activity

Abstract: The novel low molecular weight chitosan polysulfate (MW 5,120–26,200 Da) was prepared using the depolymerization of chitosan with papain (EC. 3.4.22.2). The sulfonation of depolymerized products was performed using chlorosulfonic acid in N, N-dimethylformamide under semi-heterogeneous conditions. The structures of the products were characterized by FTIR, 13C NMR, and 1H NMR (1D, 2D NMR) spectroscopy. The present study sheds light on the mechanism of anticoagulant activity of chitosan polysulfate. Anticoagulant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 27 publications
5
47
0
Order By: Relevance
“…This behaviour indicates that the non-existence of free amino groups is (Gamzazade et al, 1997) that have used the same synthesis procedure to produce the substitution of the sulphate group in hydroxide and amino groups, but not with a 100% of substitution. On the other hand, other studies (Suwan et al, 2009) also show the inclusion of the sulphate group in both kinds of centres with a 100% of inclusion, which is in agreement with the results obtained in this work. The behaviours commented in relation to the titration curves shown in Figure 1 allows us the calculation of the polymers deacetilation degree using Equation (1) (see material and methods section), which are shown in Table 2.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…This behaviour indicates that the non-existence of free amino groups is (Gamzazade et al, 1997) that have used the same synthesis procedure to produce the substitution of the sulphate group in hydroxide and amino groups, but not with a 100% of substitution. On the other hand, other studies (Suwan et al, 2009) also show the inclusion of the sulphate group in both kinds of centres with a 100% of inclusion, which is in agreement with the results obtained in this work. The behaviours commented in relation to the titration curves shown in Figure 1 allows us the calculation of the polymers deacetilation degree using Equation (1) (see material and methods section), which are shown in Table 2.…”
Section: Resultssupporting
confidence: 93%
“…On the other hand, the opposite behaviour is observed for chitosan sulphate: a decrease in the molecular weight when compared to the chitosan. This different behaviour is due to the fact that the reaction between chlorosulphonic acid produces an aggressive chemical reaction with chitosan that causes the rupture of polymer chains, in agreement with previous studies (Suwan et al, 2009) that had observed a decrease of the molecular weight close to 99% when the chemical reaction between these compounds was performed for 5 h. The chemical reaction was performed for only 1 h in this work, and for this reason, the reduction in the molecular weight was low. The present work also studies the flow behaviour of different aqueous solutions corresponding to the polymers previously analysed, taking into account the exceptional importance of this physical property upon different industrial operations (Á lvarez, Sanjutjo, Cancela, & Navaza, 2000;Jiao, Xueqiong, & Juntag, 1998;Sovilj & Petrovi, 2007).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Present investigation, in invitro anticoagulant potential and the levels of coagulation factors were assayed in normal human plasma with APTT, PT and TT reagents. In humans, normal hemostasis depends on the complex interaction of clotting of blood plasma and aggregation of platelets through the release of clotting factors [21]. The APTT assay measures the activity of all coagulation factors in the intrinsic pathway.…”
Section: Anticoagulant Activitymentioning
confidence: 99%